ANALISIS KETERLIBATAN PERILAKU SISWA DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Laila Alifah, Kurnia Nurvina; Sukiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Behavioral engagement is an important aspect of mathematics learning in elementary schools because it reflects students’ active participation during the learning process. This study aims to analyze students’ behavioral engagement in mathematics learning at the elementary school level. The study employed a qualitative approach with a descriptive research design. Data were collected through observations and interviews with fifth-grade elementary school students. Observations were conducted to examine students’ behavioral engagement during mathematics learning, while interviews were used to explore students’ experiences and responses to learning activities. Data analysis was carried out through data reduction, data display, and conclusion drawing. The results indicate that students’ behavioral engagement in mathematics learning varies. Some students demonstrated active behavioral engagement, such as attempting to solve problems independently, asking questions when experiencing difficulties, and checking their work. However, other students tended to wait for examples or guidance from the teacher before actively engaging in learning activities. These findings suggest that students’ behavioral engagement is influenced by learning habits and instructional strategies implemented by teachers. Therefore, mathematics learning should be designed to encourage active student participation so that students’ behavioral engagement can develop optimally